Mechanisms and molecular characterization of relapsed/refractory neuroblastomas - Chen, Chong; Wei, Zixuan (Frontiers in Oncology, 2025)
Relapsed/refractory neuroblastoma is a type of malignant solid tumor with a very poor prognosis in children. Its pathogenesis is complex, involving multiple molecular pathways and genetic alterations. Recent studies have shown that MYCN amplification, ALK mutation, TERT promoter mutation, p53 pathway inactivation, and chromosomal instability are the key mechanisms and molecular characteristics of relapsed/refractory neuroblastoma. Precision treatment strategies targeting these molecular mechanisms have shown certain prospects in preclinical studies and clinical practice. This review focuses on the relevant mechanisms and molecular characteristics of relapsed/refractory neuroblastoma, explores its relationship with treatment response and clinical prognosis, and briefly introduces the current treatment strategies to provide a theoretical basis for the development of novel and personalized therapeutic regimens to improve the prognosis of children.